PYOMETRA IN A FEMALE LION (Panthera leo): REPORT of CASE. - Fornazari, Felipe; Teixeira, Carlos Roberto [UNESP]; Rahal, Sheila Canevese [UNESP]; Faccioli, Patricia Yoshida; Almeida, Patricia Helena Nogueira; Langoni, Hélio [UNESP] (My University, 2011)
Pyometra is a common disease of intact bitches that may also occur in large wild cats. The present study describes a case of pyometra in female lion (Panthera leo). The animal was referred with a vulvar discharge; physical examination and complementary exams did not show abnormalities. An ovariohysterectomy was performed, and the uterus reveals a thick endometrium with purulent/sanguinolent fluid. The bacterial culture resulted in Escherichia coli. The animal had an excellent recovery.